Daliranite, PbHgAs2S5: determination of the incommensurately modulated structure and revision of the chemical formula. Issue 4 (9th August 2019) - Lanza, Arianna E.; Gemmi, Mauro; Bindi, Luca; Mugnaioli, Enrico; Paar, Werner H.
Abstract : The modulated crystal structure of the mineral daliranite has been determined using 3D electron diffraction on nanocrystalline domains. Abstract : The incommensurately modulated crystal structure of the mineral daliranite has been determined using 3D electron diffraction data obtained on nanocrystalline domains. Daliranite is orthorhombic with a = 21, b = 4.3, c = 9.5 Å and shows modulation satellites along c . The solution of the average structure in the Pnma space group together with energy‐dispersive X‐ray spectroscopy data obtained on the same domains indicate a chemical formula of PbHgAs2 S5, which has one S fewer than previously reported. The crystal structure of daliranite is built from columns of face‐sharing PbS8 bicapped trigonal prisms laterally connected by [2+4] Hg polyhedra and (As 3+ 2 S5 ) 4− groups. The excellent quality of the electron diffraction data allows a structural model to be built for the modulated structure in superspace, which shows that the modulation is due to an alternated occupancy of a split As site.